Rock magnetic and geochemical evidence for authigenic magnetite formation via iron reduction in coal‐bearing sediments offshore Shimokita Peninsula, Japan (IODP Site C0020). (14th June 2017) - Phillips, Stephen C.; Johnson, Joel E.; Clyde, William C.; Setera, Jacob B.; Maxbauer, Daniel P.; Severmann, Silke; Riedinger, Natascha
Abstract: Sediments recovered at Integrated Ocean Drilling Program (IODP) Site C0020, in a fore‐arc basin offshore Shimokita Peninsula, Japan, include numerous coal beds (0.3–7 m thick) that are associated with a transition from a terrestrial to marine depositional environment. Within the primary coal‐bearing unit (∼2 km depth below seafloor) there are sharp increases in magnetic susceptibility in close proximity to the coal beds, superimposed on a background of consistently low magnetic susceptibility throughout the remainder of the recovered stratigraphic sequence. We investigate the source of the magnetic susceptibility variability and characterize the dominant magnetic assemblage throughout the entire cored record, using isothermal remanent magnetization (IRM), thermal demagnetization, anhysteretic remanent magnetization (ARM), iron speciation, and iron isotopes. Magnetic mineral assemblages in all samples are dominated by very low‐coercivity minerals with unblocking temperatures between 350 and 580°C that are interpreted to be magnetite. Samples with lower unblocking temperatures (300–400°C), higher ARM, higher‐frequency dependence, and isotopically heavy δ 56 Fe across a range of lithologies in the coal‐bearing unit (between 1925 and 1995 mbsf) indicate the presence of fine‐grained authigenic magnetite. We suggest that iron‐reducing bacteria facilitated the production of fine‐grained magnetite within the coal‐bearing unit during burial and interaction with pore waters. The coal/peat acted as a source of electron donors during burial, mediated by humic acids, to supply iron‐reducing bacteria in the surrounding siliciclastic sediments. These results indicate that coal‐bearing sediments may play an important role in iron cycling in subsiding peat environments and if buried deeply through time, within the subsequent deep biosphere. Key Points: Increased magnetic susceptibility was observed associated with a deeply buried (∼2 km) coal‐bearing unit Rock magnetic/geochemical properties indicate that fine‐grained magnetite within the coal‐bearing unit increases magnetic susceptibility Peat/lignite was likely source of electron donors during burial to fuel production of fine‐grained, authigenic magnetite via iron reduction